ABATACEPT: A NEW CHOICE FOR CHILDREN WITH POLYARTICULAR COURSE JUVENILE IDIOPATHIC ARTHRITIS - N. Ruperto ("Paediatrician" Publishers LLC, 2010)
Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disorder in children. Children with polyarticular curse JIA, who do not respond to non-steroidal anti-inflammatory drugs and steroid injections, are treated with disease modyfing anti-rheumatic drugs with the first choice being methotrexate (MTX). For children not responding or intolerant to MTX, different therapeutic modalities with the so-called biologic agents, such as anti-tumor necrosis factor (TNF), are now available. However, a certain proportion of children with JIA, do not respond or are intolerant to anti-TNF therapy. This review summarises the available evidence related to the safety and efficacy profile of abatacept, a new selective co-stimulation modulator, for the treatment of polyarticular course JIA.Key words: children, juvenile idiopathic arthritis, juvenile rheumatoid arthritis, abatacept, inactive disease status, T-cell co-stimulation.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):32-39)